Lung Cancer Screening in the Community Setting: Challenges for Adoption. Issue 9 (September 2018) - Randhawa, Simran; Drizin, Gary; Kane, Tracy; Song, Grace Y.; Reilly, Thomas; Jarrar, Doraid
Secondary prevention of lung cancer by screening a high-risk population with low-dose CT (LDCT) of the chest has been shown to save lives. Our Institution offered a free screening program in 2013. The program was promoted through flyers, radio programs, face-to-face information sessions, and a multidisciplinary lung symposium. A lung navigator confirmed the eligibility of patients according to National Lung Screening Trial (NLST) criteria. Data were, prospectively, collected over a 12-month period using Lung-RADs (Lung Imaging Reporting and Data System). After one year, an online survey was sent out to all primary care and referring physicians in the network. One hundred and sixty-nine patients were found to be eligible for screening. Sixty-five per cent were black, 44 per cent white, 9 per cent Hispanic, and 6 per cent were Asian. Sixty per cent patients were referred by their physician. Thirty-one were Lung-RADs 1 (18.3%), 116 were Lung-RADs 2 (68.6%), 16 were Lung-RADs 3 (9.5%), and six were Lung-RADs 4 (3.6%). At the end of the study period, the survey showed that 100 per cent of the providers were aware of the screening program but 15 per cent never referred a patient. Time constraints and requirement for precertification were cited as potential barriers to referral. Twenty-six per cent of providers were unaware that LDCT was recommended by the U.S. Preventive Services Task Force on par with colonoscopy and mammography. The NLST showed that screening with LDCT could reduce lung cancer mortality by 20 per cent. Significant concerns exist about the generalizability of these results and the applicability of screening programs in the community.